2020
DOI: 10.1186/s13568-020-00986-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of catalpol against apoptosis in cardiomyocytes derived from human induced pluripotent stem cells

Abstract: Cardiac arrhythmia is an irregular heart rhythm that can lead to serious heart conditions and various organ disorders, and may cause sudden cardiac death. Catalpol belongs to the iridoid glycoside family and is highly abundant in Rehmannia glutinosa Libosch. The study included five groups such as group I (normal control), group II (treatment control), group III (low-dose treatment), group IV (medium-dose treatment) and group V (high-dose treatment). We investigated the therapeutic effects of catalpol on cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Human induced pluripotent stem cells (iPSC) are cultured and differentiated into cardiomyocytes. Then, catalpol is incubated with iPSC for 24 h. Catalpol (10 and 100 μM) significantly improved the cell viability and decreased the LDH levels in arrhythmia [ 122 ]. Catalpol (10 and 100 μM) significantly reduced lipid peroxidation in iPSC and also successfully attenuated oxidative stress by increasing SOD, Gpx, and GSH.…”
Section: Effects Of Catalpol In Diabetes Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human induced pluripotent stem cells (iPSC) are cultured and differentiated into cardiomyocytes. Then, catalpol is incubated with iPSC for 24 h. Catalpol (10 and 100 μM) significantly improved the cell viability and decreased the LDH levels in arrhythmia [ 122 ]. Catalpol (10 and 100 μM) significantly reduced lipid peroxidation in iPSC and also successfully attenuated oxidative stress by increasing SOD, Gpx, and GSH.…”
Section: Effects Of Catalpol In Diabetes Complicationsmentioning
confidence: 99%
“…Catalpol (10 and 100 μM) significantly reduced lipid peroxidation in iPSC and also successfully attenuated oxidative stress by increasing SOD, Gpx, and GSH. The activities of caspase 3 and caspase 9 are also decreased by catalpol, indicating catalpol has attenuated apoptosis [ 122 ]. However, these activities need to be further established using in vivo arrhythmia model.…”
Section: Effects Of Catalpol In Diabetes Complicationsmentioning
confidence: 99%
“…The most frequently used herb for PV is Radix Rehmanniae Recens. Catalpol is the main component of Radix Rehmanniae Recens, and it could improve the lesion of psoriasis by alleviating oxidative stress, activation of AMPK-mediated mitochondrial biogenesis, up-regulating expressions of cleaved Caspase-3 and PARP (31)(32)(33). The main component of Radix Salviae Miltiorrhizae, Tanshinone IIA has been confirmed its ability of anti-psoriasis.…”
Section: Potential Pharmacological Mechanisms Of Action Of Tcm Ingredmentioning
confidence: 92%
“…Moreover, in specific autopsy instances of AC poisoning, it has been noted that myocarditis or significant damage to the heart muscle were evident. Additionally, preclinical investigations have demonstrated that AC exhibits cytotoxic properties towards cardiomyocytes, akin to those observed in cases of acute myocardial infarction ( Yang et al, 2020 ). Furthermore, the manifestation of acute AC poisoning often encompasses palpitations, hypotension, bradycardia, and sinus tachycardia, which are characteristic cardiovascular symptoms ( Zhao et al, 2016 ).…”
Section: Pharmacological Activities Of Acmentioning
confidence: 99%